CAUSES OF NORMAL SPEECH DEVELOPMENT AND DISORDER IN CHILDREN (International journal of artificial intelligence, 2025)
In the article, the reasons for the normative development of children's speech, the causes of disorders, and the ways of developing skills are determined.